Improving Mathematics Learning Outcomes about Rectangular and Rectangular Flat Shape using Plated Paper and Stick Props Class III Elementary School - Fakhruddin, Wahidatun Mukarromah (Universitas Sebelas Maret, 2022)
There are various factors that cause students' lack of success in understanding Mathematics lessons.one of which is the delivery method and the methods used. A mechanistic or direct method of delivery by giving rules to memorize.remember and apply. Teachers do not use and utilize teaching aids that can help achieve learning objectives. Therefore.teachers are expected to look for alternative improvements.one of which is by using teaching aids that can be used as a bridge to make it easier for students to think. This research aims to improve mathematics learning outcomes about square and rectangular figures through the use of sticks and checkered paper at SD N 1 Drono class III for the 2013/2014 academic year. This research is Classroom Action Research (PTK) which was conducted to improve students' abilities in learning mathematics. The process of implementing class actions goes through 4 stages in 2 cycles.namely starting from planning (1).Action (2).Observation (3).and Reflection (4). From the results of the research carried out.it can be concluded that: Using stick props and checkered paper can improve mathematics learning outcomes about square and rectangular shapes in class III at SD N 1 Drono. Where these teaching aids can also increase students' creativity and increase students' active participation in thinking.